2019
DOI: 10.1515/ntrev-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of nano-sized carbon black for reinforcement of rubber

Abstract: The standard sample IRB7# of nano-sized carbon black was reated by different methods, including washing by alcohol, toluene, water, the emulsion of toluene and water, and heating. Surface activity of the obtained nanoparticles was measured using inverse gas chromatography. The results showed that the dispersion free energy could be significantly increased after heating. The surface activity of three kinds of industrial carbon black was studied after heat treatment at different temperature. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…where VEC i is the VEC of each component and c i is the concentration of each component in Co 28 In addition, the formation and the stability of the solid solution can be predicted by the enthalpy of mixing, and the previous studies found that the formation of phases and the segregation of the elements could be determined by the enthalpy of mixing between the elements [53,54]. The enthalpy of mixing between the elements is presented in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…where VEC i is the VEC of each component and c i is the concentration of each component in Co 28 In addition, the formation and the stability of the solid solution can be predicted by the enthalpy of mixing, and the previous studies found that the formation of phases and the segregation of the elements could be determined by the enthalpy of mixing between the elements [53,54]. The enthalpy of mixing between the elements is presented in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the change situation of Fe, Co, Ni, Cr, and Mo elements is shown in Figure 9. Compared with as-sintered alloys, the contents of Fe, Co, Ni, Cr, and Mo elements in the FCC phase and μ phase do not change much, indicating that annealing at low temperature has no obvious influence on the chemical composition of microstructure inCo 28 respectively. The SEM-BSE images of the microstructure in as-annealed alloys are shown in Figure 10a-c.…”
Section: Materials Characterizationmentioning
confidence: 95%
See 3 more Smart Citations